Comparison of the efficacy of tenofovir and entecavir for the treatment of nucleos(t)ide-naive patients with chronic hepatitis B - Ümit Bilge Doğan; Banu Kara; Yüksel Gümürdülü; Aliye SOYLU; Mustafa Salih Akın (Turkish Journal of Gastroenterology, 2019)
-